Notebook writing and student attitude toward physics - Nada, Felix B. (2008)
This study was conducted to look into the students' writings in high school physics notebooks. The study combined exploratory and correlational research design utilizing both qualitative and quantitative approaches. The constructed attitude survey scale test was administered to 30 randomly selected high school students coming from 5 different types of secondary schools in Manila and representing varying academic proficiency levels. Findings revealed that students' science notebooks contain 5 major writing entries--assignment, lecture notes, seatwork, personal note/outline, and extra. Five different forms of scientific communication--verbal, schematic, pictorial, symbolic, and numerical--were identified. Though students generally showed positive attitude toward physics and science writing, results revealed non-significant correlation of both aspects to teacher feedback.
Thesis (M.A. Physics Education)--University of the Philippines, Diliman.
Keywords: Physics -- Study and teaching (Secondary) -- Philippines -- Manila Metropolitan Area; High school students -- Philippines -- Manila Metropolitan Area -- Attitudes; Physics -- Laboratory manuals; Technical writing -- Philippines